Ugniatanie materii słownej „jak ogromnej dzieży ciasta”, czyli schulzowskie porównania w tłumaczeniu na język hiszpański - Galant, Barbara (Acta Neophilologica, 2019)
One of the markers of Bruno Schulz’s style is the simile. It plays two roles in the poetic prose of the author: on the one hand, it confronts two phenomena in a concise and conventional manner; on the other, it compares, quite unexpectedly, two events, living creatures or objects, which seem to have nothing in common. In this article I analyze excerpts of three Spanish translations in order to identify techniques used to render this trope, to verify the consequences of the omission of the linking words, and to investigate whether Spanish readers will be able to recreate the same or a similar image to the one evoked in the original.